Adhesive tape for semiconductor wafer thinning and preparation process thereof

By using a combination of a polyolefin substrate layer and a modified acrylic adhesive layer, the problems of insufficient rigidity of the substrate layer and high-temperature softening during wafer thinning are solved, achieving stable fixation and protection of the wafer, reducing the risk of warping and cracking, and improving the reliability and cleanliness of the process.

CN121045980AActive Publication Date: 2025-12-02TAICANG DIKELI TECH CO LTD

Patent Information

Application Number
CN202511604047.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-05
Publication Date
2025-12-02
Estimated Expiration
2045-11-05

AI Technical Summary

Technical Problem

Existing wafer thinning tapes have insufficient rigidity of the substrate layer during high-temperature grinding, resulting in uneven stress on the wafer and problems such as warping, cracking, and residual adhesive. Furthermore, the thermoplastic polyurethane substrate layer is prone to softening and deformation at high temperatures, losing its fixing and protective functions.

Method used

The material employs a polyolefin substrate layer and a modified acrylic adhesive layer. The polyolefin substrate layer, by controlling its crystallinity, combines moderate rigidity and elasticity to resist mechanical pressure. The modified acrylic adhesive layer enhances adhesion through polar groups and a crosslinking system. Combined with plasma treatment and modifiers, a rigid skeleton-flexible connection-gap filling structure is constructed to enhance fixation and protection capabilities.

Benefits of technology

It effectively prevents uneven stress on the wafer, reduces the risk of localized thinning or cracking, improves fixation stability and protection, and ensures the convenience and cleanliness of subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of semiconductor wafer processing, and particularly discloses an adhesive tape for semiconductor wafer thinning and a preparation process thereof. The adhesive tape for semiconductor wafer thinning comprises a base material layer and a bonding layer arranged on the surface of the base material layer, the base material layer is made of polyolefin, and the bonding layer is a modified acrylic acid adhesive layer; the modified acrylic acid adhesive layer is prepared from the following raw materials in parts by weight: 60 to 70 parts of 2-ethylhexyl acrylate, 15 to 25 parts of butyl acrylate, 5 to 10 parts of methyl methacrylate, 2 to 5 parts of hydroxyethyl acrylate, 0.5 to 2 parts of glycidyl methacrylate, 1 to 3 parts of a modifier, 0.8 to 1.2 parts of an isocyanate cross-linking agent, 0.3 to 0.8 part of an epoxy cross-linking agent and 0.3 to 0.8 part of azodiisobutyronitrile. According to the adhesive tape for semiconductor wafer thinning, the fixing and protecting effects on the wafer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor wafer processing technology, and more specifically, to a semiconductor wafer thinning tape and its preparation process. Background Technology

[0002] With technological advancements, electronic products are becoming smaller and more powerful. For example, the chips in mobile phones and smartwatches require increasingly thinner wafers. Thinning wafers allows for thinner chip packaging, better heat dissipation, and reduced signal transmission latency, meeting the demands of advanced technologies. Wafer thinning is mostly achieved through mechanical grinding, a highly efficient and low-cost method. However, during grinding, the wafer is subjected to pressure, friction, and heat, which can easily lead to warping, cracks, and silicon powder adhering to the surface, affecting subsequent processing. To avoid these problems, the industry uses wafer thinning tape applied to the front side of the wafer with circuitry to secure it and prevent displacement or damage during grinding. After thinning, the tape is removed using methods such as heating or ultraviolet light.

[0003] Patent application CN119019947A discloses a photocurable wafer polishing protective tape and its preparation method, as well as a wafer thinning method. The photocurable wafer polishing protective tape comprises an adhesive layer and a substrate layer. The substrate layer is made of thermoplastic polyurethane to facilitate wafer dicing. The adhesive layer comprises the following components by weight percentage: 61%-63% modified acrylic resin, 1.5%-3.5% hardener, 1.0%-2.5% photoinitiator, 3.1% delay catalyst, 0.3% organic nano-color powder, and 30%-32% solvent. This patent improves the film-forming properties and hardness of the adhesive layer by adjusting the ratio of modified acrylic resin to hardener and photoinitiator, and by combining delayed catalyst, organic nano-pigment, and solvent, thereby reducing the adhesion to the wafer and controlling the peel force between the wafer grinding protective tape and the wafer. This enhances the protective effect of the wafer grinding protective tape on the wafer during the grinding and thinning process. However, the use of thermoplastic polyurethane (TPU) as the substrate layer presents several challenges. First, while TPU is flexible, it lacks rigidity. The mechanical pressure during grinding can cause the middle area of ​​the substrate layer to sink, resulting in uneven stress on the wafer and localized thinning or cracks. Second, the grinding process generates heat (typically 50-100℃, but can reach over 200℃ for silicon carbide wafers). TPU has a low glass transition temperature (mostly between -50℃ and 80℃), making it prone to softening and deformation at high temperatures. This leads to a decrease in the bonding force between the substrate layer and the adhesive layer, and even delamination, resulting in a loss of the wafer's fixation and protection. Summary of the Invention

[0004] To improve the fixing and protection effect of semiconductor wafer thinning tape on wafers, this application provides a semiconductor wafer thinning tape and its preparation process.

[0005] In a first aspect, this application provides a semiconductor wafer thinning tape, employing the following technical solution: A semiconductor wafer thinning tape includes a substrate layer and an adhesive layer disposed on the surface of the substrate layer, wherein the substrate layer is made of polyolefin and the adhesive layer is a modified acrylic adhesive layer. The modified acrylic adhesive layer comprises the following raw materials in parts by weight: 60-70 parts of isooctyl acrylate, 15-25 parts of butyl acrylate, 5-10 parts of methyl methacrylate, 2-5 parts of hydroxyethyl acrylate, 0.5-2 parts of glycidyl methacrylate, 1-3 parts of modifier, 0.8-1.2 parts of isocyanate crosslinking agent, 0.3-0.8 parts of epoxy crosslinking agent, and 0.3-0.8 parts of azobisisobutyronitrile.

[0006] By adopting the above technical solution, the substrate layer is made of polyolefin, which not only avoids high-temperature softening and deformation due to its high temperature resistance, but also has moderate rigidity and elasticity by controlling the crystallinity. This resists the pressure of grinding machinery to prevent uneven stress on the wafer caused by substrate depression, reduces the risk of local thinning or cracking, and strengthens support and fixation stability. The adhesive layer uses isooctyl acrylate and butyl acrylate as the main soft monomers to ensure flexibility, and combines them with methyl methacrylate to improve strength. Relying on the polar groups and double crosslinking system of hydroxyethyl acrylate and glycidyl methacrylate, reliable adhesion to the wafer is achieved during grinding to prevent displacement. At the same time, the surface energy is reduced by the modifier to adapt to the requirements of non-UV heat peeling, and there is no migratory organic nano-color powder added to reduce impurity contamination. Ultimately, while improving the fixation and protection of the wafer, it also takes into account the convenience and cleanliness of subsequent processing.

[0007] Preferably, the polyolefin is one of polyethylene and polypropylene, and more preferably polyethylene.

[0008] By adopting the above technical solutions, from the perspective of molding and processing, polyethylene has better melt flowability than polypropylene, making it easier to control the thickness uniformity during extrusion and casting film formation. Furthermore, it requires lower processing temperatures, reducing energy consumption and the risk of thermal damage to the substrate. From the perspective of mechanical property compatibility, polyethylene has better low-temperature toughness than polypropylene. The resulting substrate layer is less prone to cracking or damage due to low temperatures or external bending during subsequent coating, winding, and tape use. Polypropylene, on the other hand, is prone to embrittlement below 0°C and has poor adaptability to low-temperature applications. In addition, the raw material cost of polyethylene is usually slightly lower than that of polypropylene, and no additional antioxidants are needed during molding to improve aging resistance, giving it a cost and process stability advantage in substrate layer production.

[0009] Preferably, the substrate layer is prepared by: extruding and casting linear low-density polyethylene to obtain a film, and then subjecting the film to plasma treatment under conditions of vacuum of 20-30 Pa, oxygen flow of 15-20 sccm, and radio frequency power of 100-120 W to obtain the substrate layer.

[0010] By adopting the above technical solution, linear low-density polyethylene itself, relying on its low crystallinity characteristics, has moderate elasticity and stable mechanical properties. It can buffer mechanical vibration and local stress during wafer grinding, and avoid edge damage or surface circuit scratches on hard and brittle wafers such as Si and SiC due to concentrated stress.

[0011] In particular, plasma treatment can remove residual oil and low-molecular-weight volatiles after linear low-density polyethylene film extrusion casting, improve the surface cleanliness of the substrate, and introduce polar groups to overcome the limitations of the inertness of the LLDPE surface, ensuring strong adhesion with modified acrylic adhesives.

[0012] Preferably, the substrate layer is prepared by mixing linear low-density polyethylene, metallocene polyethylene and hindered phenolic antioxidant in a mass ratio of (88-90):(10-12):(0.03-0.05) and extruding and casting to obtain a film, and then subjecting the film to plasma treatment under vacuum of 20-30 Pa, oxygen flow rate of 15-20 sccm and radio frequency power of 100-120 W to obtain the substrate layer.

[0013] By adopting the above technical solution, adding an appropriate amount of metallocene polyethylene to the substrate layer can disrupt the crystalline region arrangement of LLDPE with its regular and uniformly branched molecular chains, thereby reducing the crystallinity of the substrate. This not only maintains high tensile strength to meet support requirements, but also gives the substrate appropriate elasticity by increasing the proportion of amorphous regions, which can effectively buffer mechanical vibration and local stress during wafer grinding. At the same time, the branches of metallocene polyethylene can optimize the microstructure of the substrate surface and improve the effect of subsequent plasma treatment.

[0014] Preferably, the modifier comprises the following raw materials in parts by weight: 0.5-1.5 parts acrylate-terminated polydimethylsiloxane, 0.3-0.8 parts methacryloxyPOSS and 0.3-1.0 parts hydroxylated nanofiller.

[0015] Preferably, the modifier is prepared by adding hydroxylated nanofiller to a solvent and dispersing it ultrasonically, then adding methacryloyloxy POSS and dispersing it ultrasonically, and finally adding acrylate-terminated polydimethylsiloxane and dispersing it ultrasonically to obtain the modifier.

[0016] By employing the above technical solution, the cage-like structure of methacryloxy POSS serves as a nanonode, forming a network structure with the long chains of acrylate-terminated polydimethylsiloxane through point-to-line connections. Simultaneously, nanofillers fill the gaps in the network, forming hydrogen bonds with polar groups in the adhesive through hydroxyl groups. These three elements synergistically construct a composite structure of rigid framework, flexible connections, and gap filling, enhancing cohesion. This composite modification system, through the synergistic effect of the three modifiers, significantly improves the reliability of wafer fixation and protection during the grinding process while maintaining the simplicity of non-UV tape processing, making it particularly suitable for high-precision semiconductor thinning processes.

[0017] Preferably, the hydroxylated nanofiller is prepared by using a sol-gel method to obtain nano-silica, followed by surface modification with a silane coupling agent.

[0018] By adopting the above technical solution, this application uses the sol-gel method to obtain nano-silica, which is then modified with a silane coupling agent to introduce double bond groups compatible with acrylic resin on the surface of the nanoparticles, thereby greatly improving its interfacial bonding force with the adhesive matrix. Moreover, the overall process is conventional, controllable, and highly repeatable.

[0019] Preferably, the hydroxylated nanofiller is prepared by sol-gel method to obtain nano-silica and nano-alumina, and then the nano-silica and nano-alumina are mixed and surface modified with silane coupling agent.

[0020] By adopting the above technical solutions, on the one hand, hydroxylated silica, with its high-density surface hydroxyl groups, forms strong hydrogen bonds and covalent bonds with the hydroxyl groups of hydroxyethyl acrylate and the epoxy groups of glycidyl methacrylate in the adhesive, significantly improving the cohesive force and interfacial adhesion of the adhesive layer, ensuring firm fixation and no risk of detachment during wafer polishing; on the other hand, the strong-curing modified nano-alumina, relying on its high rigidity, can enhance the wear resistance and scratch resistance of the adhesive layer, effectively resisting the damage to the wafer surface circuitry caused by mechanical stress during polishing. At the same time, its hydroxylated surface energy can synergistically construct a uniformly dispersed three-dimensional reinforcement network with silica, which absorbs polishing vibration energy and reduces wafer stress concentration through the buffer-rigid support synergistic effect, while avoiding local defects caused by nanoparticle agglomeration, improving the efficient fixation and reliable protection of the wafer and subsequent easy peeling.

[0021] Secondly, this application provides a process for preparing a semiconductor wafer thinning tape, which adopts the following technical solution: A process for fabricating a semiconductor wafer thinning tape includes the following steps: Mix the monomer, solvent, and initiator according to the formula, react at 60-70℃ for 4-6 hours under nitrogen protection, raise the temperature to 75℃ and keep it at that temperature for 1 hour; cool down to below 40℃, add the modifier and crosslinking agent and stir evenly to obtain the adhesive. The adhesive is applied as a base coat to the substrate layer using a microgravure coating method, and then as a top coat using a transfer coating method to obtain a tape for thinning semiconductor wafers.

[0022] By adopting the above technical solution, the primer is formed on the substrate surface through micro-gravure coating to form a thin and uniform base layer, which can not only enhance the adhesion between the substrate and the subsequent adhesive layer, but also adjust the surface properties of the substrate, laying a stable foundation for the topcoat. The topcoat is transferred to the surface of the composite material by using a doctor blade transfer coating, which not only achieves uniform control of the adhesive film thickness, but also reduces the risk of total thickness fluctuation by taking advantage of the fact that the thickness of the adhesive layer depends on the thickness deviation of the composite material. The combination of the two solves the problem of bonding between the substrate and the functional adhesive layer, and ensures the accuracy and functional integrity of the final adhesive layer, so that the tape can have good adhesion, dimensional stability and core performance.

[0023] Preferably, the substrate layer is subjected to corona treatment at a power of 300-350W and a speed of 10-15m / min before coating.

[0024] By adopting the above technical solution, corona treatment can quickly and efficiently improve the surface tension of the substrate layer and enhance the adhesion to the coating.

[0025] In summary, this application has the following beneficial effects: 1. The substrate layer of this application is made of polyolefin, which not only avoids high-temperature softening and deformation due to its high temperature resistance, but also has moderate rigidity and elasticity by controlling the crystallinity. It resists the pressure of grinding machinery to prevent uneven stress on the wafer caused by substrate depression, reduces the risk of local thinning or cracking, and strengthens the support and fixation stability.

[0026] 2. This application performs plasma treatment on the substrate layer, which can remove residual oil and low-molecular-weight volatiles after linear low-density polyethylene film extrusion casting, improve the surface cleanliness of the substrate, and introduce polar groups to improve the adhesion between the substrate layer and the adhesive layer.

[0027] 3. The modifier in this application is a compound of acrylate-terminated polydimethylsiloxane, methacryloxyPOSS and hydroxylated nanofiller. The three work together to construct a composite structure of rigid skeleton-flexible connection-gap filling, which improves the reliability of wafer fixation and protection during the grinding process. Detailed Implementation

[0028] The present application will be further described in detail below with reference to the embodiments.

[0029] Unless otherwise specified, the raw materials used in the embodiments and comparative examples of this application are all commercially available.

[0030] Example Example 1 This embodiment provides a semiconductor wafer thinning tape, which consists of a substrate layer and an adhesive layer disposed on the surface of the substrate layer from top to bottom. The adhesive layer is a modified acrylic adhesive layer, which is made from the following raw materials: 60 kg of isooctyl acrylate, 25 kg of butyl acrylate, 5 kg of methyl methacrylate, 2 kg of hydroxyethyl acrylate, 2 kg of glycidyl methacrylate, 1 kg of modifier, 0.8 kg of hexamethylene diisocyanate trimer, 0.8 kg of AG-602 epoxy crosslinking agent, 0.3 kg of azobisisobutyronitrile, 240 kg of ethyl acetate, and 60 kg of propylene glycol methyl ether acetate. The modifier is PDMS-25 dimethacrylate (CAS: 70877-62-2).

[0031] This embodiment also provides a process for preparing the above-mentioned semiconductor wafer thinning tape, including the following steps: Substrate layer preparation: Linear low-density polyethylene granules (SABIC®) with a melt flow rate of 3 g / 10 min are prepared. LLDPE319BJ was dried in a 70℃ oven for 3 hours, then extruded and cast in a single-screw extruder to obtain a substrate film. Specifically, the extruder temperature was set as follows: 140-160℃ for the hopper zone, 160-175℃ for the second zone, 170-185℃ for the third zone, and 180-190℃ for the die head. After reaching the set temperature, the temperature was maintained for 30 minutes. The material was fed at a screw speed of 45 r / min. After the die head stably extruded a melt without bubbles or coke particles, the casting roller and traction system were started to guide the melt to the casting roller for cooling and shaping at a speed of 10 m / min. At the same time, the traction tension was controlled at 100 N. Finally, the film was wound up to obtain a substrate film with a thickness of 50 μm. The substrate film was cut into rolls that matched the width of the coating machine. The surface of the substrate was wiped with anhydrous ethanol and then dried in a 60℃ oven for 10 minutes to obtain the substrate layer. Preparation of adhesive: According to the above formula, weigh isooctyl acrylate, butyl acrylate, methyl methacrylate, hydroxyethyl acrylate, glycidyl methacrylate, ethyl acetate, propylene glycol methyl ether acetate and azobisisobutyronitrile, react at 65℃ for 5h under nitrogen protection, then heat to 75℃ and keep at 75℃ for 1h. After the reaction is completed, cool down to 35℃, add modifier, hexamethylene diisocyanate trimer and AG-602 epoxy crosslinking agent, stir at 1500r / min for 30min and filter through a 100-mesh nylon filter to obtain adhesive; Preparation of the tape: A micro-gravure roller with a gravure depth of 3-5μm was selected, and the coating speed was set to 5m / min. The oven temperature was set in sections (section 1: 50℃, section 2: 70℃, section 3: 90℃, total length 3m). The adhesive was poured into the adhesive storage tank of the coating machine, the equipment was started, and the substrate was dried in the oven after the adhesive was transferred by the micro-gravure roller. After being cooled by a cooling roller at 30℃, the base coating was obtained. A silicone transfer roller with a hardness of 60-70 Shore was used, and the transfer pressure was set to 0.25MPa. The adhesive was evenly covered on the surface of the base coating by the transfer roller and put into the oven (section 1: 70℃, section 2: 90℃, section 3: 110℃, total length 6m). After drying, it was cured at 40℃ for 24h. After being cooled by a cooling roller at 25℃, it was wound up at a uniform speed with a tension of 50N. After winding, it was wrapped with polyethylene film and stored in an environment of 25℃ and 50% relative humidity.

[0032] Example 2 This embodiment is basically the same as Example 1, except that the modified acrylic adhesive layer in this embodiment is made from the following raw materials: 65 kg of isooctyl acrylate, 20 kg of butyl acrylate, 8 kg of methyl methacrylate, 4 kg of hydroxyethyl acrylate, 1 kg of glycidyl methacrylate, 2 kg of modifier, 1 kg of hexamethylene diisocyanate trimer, 0.5 kg of AG-602 epoxy crosslinking agent, 0.5 kg of azobisisobutyronitrile, 240 kg of ethyl acetate, and 60 kg of propylene glycol methyl ether acetate, wherein the modifier is PDMS-25 dimethacrylate (CAS: 70877-62-2).

[0033] Example 3 This embodiment is basically the same as Example 1, except that the modified acrylic adhesive layer in this embodiment is made from the following raw materials: 70 kg of isooctyl acrylate, 15 kg of butyl acrylate, 10 kg of methyl methacrylate, 5 kg of hydroxyethyl acrylate, 0.5 kg of glycidyl methacrylate, 3 kg of modifier, 1.2 kg of hexamethylene diisocyanate trimer, 0.3 kg of AG-602 epoxy crosslinking agent, 0.8 kg of azobisisobutyronitrile, 240 kg of ethyl acetate, and 60 kg of propylene glycol methyl ether acetate, wherein the modifier is PDMS-25 dimethacrylate (CAS: 70877-62-2).

[0034] Example 4 This embodiment is basically the same as Embodiment 2, except for the preparation of the substrate layer. Specifically, the substrate layer is prepared as follows: Linear low-density polyethylene granules (SABIC® LLDPE 319BJ) with a melt flow rate of 3 g / 10 min are dried in an oven at 70°C for 3 hours. Then, they are extruded and cast in a single-screw extruder to obtain the substrate film. Specifically, the extruder temperature is set as follows: hopper zone 140-160°C, zone 2 160-175°C, zone 3 170-185°C, and die head 180-190°C. After reaching the set values, the temperature is maintained for 30 minutes. The material is fed at a screw speed of 45 r / min. After the die head stably extrudes a melt free of bubbles and coke particles, the casting rollers and traction system are started at 10 m / m... The melt is drawn to the casting roll at a speed of in to cool and set, while the traction tension is controlled at 100N. Finally, a substrate film with a thickness of 50μm is obtained by winding. The substrate film is then subjected to plasma treatment under the conditions of vacuum degree of 20Pa, oxygen flow rate of 15sccm and radio frequency power of 100W to obtain a pretreated substrate film. The pretreated substrate film is cut into rolls that match the width of the coating machine, the surface of the substrate is wiped with anhydrous ethanol, and then dried in an oven at 60℃ for 10min to obtain the substrate layer.

[0035] Example 5 This embodiment is basically the same as Embodiment 2, except for the preparation of the substrate layer. Specifically, the substrate layer is prepared as follows: Linear low-density polyethylene granules (SABIC® LLDPE 319BJ) with a melt flow rate of 3 g / 10 min and metallocene polyethylene (ExxonMobil Exceed™ XP 8346 PA) are dried in an oven at 70°C for 3 hours. Then, 88 kg of linear low-density polyethylene granules, 12 kg of metallocene polyethylene, and 0.03 kg of 1010 antioxidant are mixed evenly and added to a single-screw extruder for extrusion and casting to obtain the substrate film. Specifically, the extruder temperature is set as follows: hopper zone 140-160°C, zone 2 160-175°C, zone 3 170-185°C, and die head 180-190°C. After reaching the set values, the temperature is maintained for 30 minutes. The material is fed at a screw speed of 45 r / min until the die head stably extrudes without bubbles or scorched particles. After melting, the casting roller and traction system are started to guide the melt to the casting roller for cooling and shaping at a speed of 10 m / min, while controlling the traction tension at 100 N. Finally, a substrate film with a thickness of 50 μm is obtained by winding. The substrate film is then subjected to plasma treatment under conditions of vacuum degree of 20 Pa, oxygen flow rate of 15 sccm, and radio frequency power of 100 W to obtain a pretreated substrate film. The pretreated substrate film is cut into rolls that match the width of the coating machine, the substrate surface is wiped with anhydrous ethanol, and then dried in an oven at 60 °C for 10 min to obtain the substrate layer.

[0036] Example 6 This embodiment is basically the same as Embodiment 5, except for the preparation of the substrate layer. Specifically, the substrate layer is prepared as follows: Linear low-density polyethylene granules (SABIC® LLDPE 319BJ) with a melt flow rate of 3 g / 10 min and metallocene polyethylene (ExxonMobil Exceed™ XP 8346 PA) are dried in an oven at 70°C for 3 hours. Then, 89 kg of linear low-density polyethylene granules, 11 kg of metallocene polyethylene, and 0.04 kg of 1010 antioxidant are mixed evenly and added to a single-screw extruder for extrusion and casting to obtain the substrate film. Specifically, the extruder temperature is set as follows: hopper zone 140-160°C, zone 2 160-175°C, zone 3 170-185°C, and die head 180-190°C. After reaching the set values, the temperature is maintained for 30 minutes. The material is fed at a screw speed of 45 r / min until the die head stably extrudes without bubbles or scorched particles. After melting, the casting roller and traction system are started to guide the melt to the casting roller for cooling and shaping at a speed of 10 m / min, while controlling the traction tension at 100 N. Finally, a substrate film with a thickness of 50 μm is obtained by winding. The substrate film is then subjected to plasma treatment under the conditions of vacuum degree of 25 Pa, oxygen flow rate of 18 sccm and radio frequency power of 110 W to obtain a pretreated substrate film. The pretreated substrate film is cut into rolls that match the width of the coating machine, the substrate surface is wiped with anhydrous ethanol, and then dried in an oven at 60 °C for 10 min to obtain the substrate layer.

[0037] Example 7 This embodiment is basically the same as Embodiment 5, except for the preparation of the substrate layer. Specifically, the substrate layer is prepared as follows: Linear low-density polyethylene granules (SABIC® LLDPE 319BJ) with a melt flow rate of 3 g / 10 min and metallocene polyethylene (ExxonMobil Exceed™ XP 8346 PA) are dried in an oven at 70°C for 3 hours. Then, 90 kg of linear low-density polyethylene granules, 10 kg of metallocene polyethylene, and 0.05 kg of 1010 antioxidant are mixed evenly and added to a single-screw extruder for extrusion and casting to obtain the substrate film. Specifically, the extruder temperature is set as follows: hopper zone 140-160°C, zone 2 160-175°C, zone 3 170-185°C, and die head 180-190°C. After reaching the set values, the temperature is maintained for 30 minutes. The material is fed at a screw speed of 45 r / min until the die head stably extrudes without bubbles or scorched particles. After melting, the casting roller and traction system are started to guide the melt to the casting roller for cooling and shaping at a speed of 10 m / min, while controlling the traction tension at 100 N. Finally, a substrate film with a thickness of 50 μm is obtained by winding. The substrate film is then subjected to plasma treatment under the conditions of vacuum degree of 30 Pa, oxygen flow rate of 20 sccm and radio frequency power of 120 W to obtain a pretreated substrate film. The pretreated substrate film is cut into rolls that match the width of the coating machine, the substrate surface is wiped with anhydrous ethanol, and then dried in an oven at 60 °C for 10 min to obtain the substrate layer.

[0038] Example 8 This embodiment is basically the same as Embodiment 6, except that the modified acrylic adhesive layer in this embodiment is made from the following raw materials: 65 kg of isooctyl acrylate, 20 kg of butyl acrylate, 8 kg of methyl methacrylate, 4 kg of hydroxyethyl acrylate, 1 kg of glycidyl methacrylate, 2 kg of modifier, 1 kg of hexamethylene diisocyanate trimer, 0.5 kg of AG-602 epoxy crosslinking agent, 0.5 kg of azobisisobutyronitrile, 240 kg of ethyl acetate, and 60 kg of propylene glycol methyl ether acetate.

[0039] The modifier is prepared using the following method: 100 mL of LTEOS was added to 400 mL of anhydrous ethanol and magnetically stirred at 300 rpm for 10 min to obtain a mixture. Dilute nitric acid was added dropwise to 600 mL of deionized water to adjust the pH to 2.5, resulting in an acidic catalyst solution. This catalyst solution was then added dropwise to the mixture, and the temperature was raised to 35 °C. Stirring was continued at 500 rpm under nitrogen protection for 5 h (samples were taken every 1 h during the reaction, and particle size was measured using a dynamic light scattering instrument to ensure PDI ≤ 0.2). After the reaction, the temperature was lowered to 25 °C, and the mixture was transferred to a dialysis bag (molecular weight cutoff 1000 Da). Dialysis was performed with deionized water for 48 h, changing the deionized water every 6 h, until the conductivity of the dialysate was ≤ 5 μS / cm to obtain a sol. The sol was concentrated to a solid content of 10% at 30 °C and -0.08 MPa, and an equal volume of deionized water was added. The mixture was stirred at 800 rpm. Stir for 30 min at -40℃ for 2 h, then dry at -50℃ and 0.01 MPa for 24 h to obtain hydroxylated nano-silica powder; prepare a solution by mixing KH-570, anhydrous ethanol and deionized water at a mass ratio of 1:10:1, adjust the pH to 4 with dilute nitric acid, and stir for 30 min to obtain a coupling agent solution; add 100 g of hydroxylated nano-silica powder to 1 L of deionized water, sonicate at 300 W and 20 kHz for 30 min, slowly add 5 g of coupling agent hydrolysate, stir at 800 r / min for 2 h at 50℃, centrifuge at 8000 r / min for 15 min, collect the precipitate; wash 3 times with anhydrous ethanol, then wash 2 times with deionized water, and dry at -50℃ and 0.01 MPa for 24 h to obtain hydroxylated modified nano-silica.

[0040] 1 kg of hydroxylated modified nano silica was added to 2.5 kg of ethyl acetate and ultrasonically dispersed at 300 W for 60 min. Then, 0.8 kg of methacryloyloxy POSS (CAS: 160185-24-0) was added and ultrasonically dispersed at 200 W for 40 min. Finally, 0.5 kg of PDMS-25 dimethacrylate (CAS: 70877-62-2) was added and ultrasonically dispersed at 150 W for 30 min to obtain the modifier. During this process, the temperature of the system was kept below 35 °C by water cooling.

[0041] Example 9 This embodiment is basically the same as Example 6, except that the preparation of the modifier is as follows: 0.7 kg of hydroxylated modified nano silica was added to 2.5 kg of ethyl acetate and ultrasonically dispersed at 300 W for 60 min. Then, 0.5 kg of methacryloyloxyPOSS (CAS: 160185-24-0) was added and ultrasonically dispersed at 200 W for 40 min. Then, 1 kg of PDMS-25 dimethacrylate (CAS: 70877-62-2) was added and ultrasonically dispersed at 150 W for 30 min to obtain the modifier. During this period, the temperature of the system was kept below 35 °C by water cooling. The preparation method of hydroxylated modified nano silica is the same as in Example 8.

[0042] Example 10 This embodiment is basically the same as Example 6, except that the modifier is prepared as follows: 0.3 kg of hydroxylated modified nano silica is added to 2.5 kg of ethyl acetate and ultrasonically dispersed at 300 W for 60 min. Then, 0.3 kg of methacryloyloxyPOSS (CAS: 160185-24-0) is added and ultrasonically dispersed at 200 W for 40 min. Then, 1.5 kg of PDMS-25 dimethacrylate (CAS: 70877-62-2) is added and ultrasonically dispersed at 150 W for 30 min to obtain the modifier. During this period, the temperature of the system is controlled by water cooling and kept below 35 °C. The preparation method of hydroxylated modified nano silica is the same as that in Example 8.

[0043] Example 11 This embodiment is basically the same as Example 10, except that the preparation of the modifier is as follows: Dissolve 5g of aluminum isobutoxide in 200mL of anhydrous ethanol. Stir magnetically at 400r / min for 30min, then add dilute nitric acid dropwise to adjust the pH to 3, forming an aluminum alkoxide solution. Add the aluminum alkoxide solution to deionized water (aluminum isobutoxide:deionized water molar ratio 1:5) and stir at 35℃ for 4h to obtain an alumina sol. After the reaction, cool to 25℃ and transfer to a dialysis bag (molecular weight cutoff 1000Da). Dialyze with deionized water for 48h, changing the deionized water every 6h, until the dialysate conductivity ≤5μS / cm to obtain the sol. Concentrate the sol to 10% solids content at 30℃ and -0.08MPa, add an equal volume of deionized water, and stir at 800r / min for 30min, repeating 3 times. Pre-freeze at -40℃ for 2h, then at -50℃ and 0.01... Hydroxylated nano-alumina powder was obtained by drying at MPa for 24 h. KH-570, anhydrous ethanol and deionized water were mixed in a mass ratio of 1:10:1 to form a solution, and the pH was adjusted to 4 with dilute nitric acid. The solution was stirred for 30 min to obtain a coupling agent solution. 99.8 g of hydroxylated nano-silica powder (prepared by the same method as in Preparation Example 8) and 0.2 g of hydroxylated nano-alumina powder were added to 1 L of deionized water and ultrasonically dispersed at 300 W and 20 kHz for 30 min. 5 g of coupling agent hydrolysate was slowly added, and the mixture was stirred at 800 r / min for 2 h at 50 °C. The mixture was then centrifuged at 8000 r / min for 15 min and the precipitate was collected. The precipitate was washed three times with anhydrous ethanol and twice with deionized water. It was then dried at -50 °C and 0.01 MPa for 24 h to obtain hydroxylated modified nanofiller.

[0044] 0.7 kg of hydroxylated modified nanofiller was added to 2.5 kg of ethyl acetate and ultrasonically dispersed at 300 W for 60 min. Then, 0.5 kg of methacryloyloxy POSS (CAS: 160185-24-0) was added and ultrasonically dispersed at 200 W for 40 min. Finally, 1 kg of PDMS-25 dimethacrylate (CAS: 70877-62-2) was added and ultrasonically dispersed at 150 W for 30 min to obtain the modifier. During this process, the temperature of the system was kept below 35 °C by water cooling.

[0045] Example 12 This embodiment is basically the same as Embodiment 11, except that in the preparation process of the tape for semiconductor wafer thinning, the tape preparation is as follows: a microgravure roller with a texture depth of 3-5 μm is selected, the coating speed is set to 5 m / min, and the oven temperature is set in segments (first segment 50℃, second segment 70℃, third segment 90℃, total length 3m); the adhesive is poured into the adhesive storage tank of the coating machine, the equipment is started, and the substrate layer is corona treated at 300W power and a speed of 10 m / min, and then the adhesive is transferred by the microgravure roller before entering the coating machine. The substrate is dried in an oven and then cooled by a cooling roller at 30°C to obtain a base coating. A silicone transfer roller with a hardness of 60-70 Shore is used, and the transfer pressure is set to 0.25 MPa. The adhesive is evenly applied to the surface of the base coating by the transfer roller. The substrate is then placed in an oven (70°C in the first section, 90°C in the second section, and 110°C in the third section, with a total length of 6m). After drying, the substrate is cured at 40°C for 24 hours. After cooling by a cooling roller at 25°C, the substrate is wound up at a uniform speed with a tension of 50N. After winding, the substrate is wrapped in polyethylene film and stored in an environment with a temperature of 25°C and a relative humidity of 50%.

[0046] Comparative Example Comparative Example 1 This comparative example is basically the same as Example 1, except that the substrate layer is prepared differently in the manufacturing process of the semiconductor wafer thinning tape. Specifically, thermoplastic polyurethane particles (Covestro TPU Desmopan) with a number average molecular weight of 20,000-30,000 are used. The 385SX TPU granules were placed in a freeze dryer and dried at -85℃ and -0.09MPa for 5 hours. Then, the dried TPU granules were added to an extruder. The temperatures of each section of the extruder were set as follows: hopper zone 110℃, feeding zone 170℃, compression zone 190℃, metering zone 200℃, and die head zone 210℃. After reaching the set temperature, the temperature was maintained for 40 minutes. The granules were fed at a screw speed of 35r / min. After the melt was extruded through the die head, it was immediately introduced into a three-section casting roller group (roller temperatures of 55℃, 45℃, and 35℃ respectively) for cooling and shaping. The melt was guided to the casting rollers for cooling and shaping at a speed of 10m / min, while controlling the traction tension at 100N. Finally, the granules were wound up to obtain a substrate film with a thickness of 50μm. The substrate film was cut into rolls that matched the width of the coating machine. The surface of the substrate was wiped with anhydrous ethanol and then dried in a 60℃ oven for 10 minutes to obtain the substrate layer.

[0047] Performance testing Testing standards: A 750 μm thick wafer was ultrasonically cleaned for 10 min using a 1:1 mixture of 1% ammonia and hydrogen peroxide, followed by drying in an 80°C oven for 5 min. The adhesive layer of the semiconductor wafer thinning tape obtained in Examples 1-12 and Comparative Example 1 was then bonded to the non-polished surface of the wafer using a vacuum laminator (lamination pressure 0.3 MPa, temperature 40°C, lamination speed 30 mm / s). The tape-coated wafer was then fixed to the vacuum chuck of a polishing machine, and the machine was started for step-by-step thinning: the first step was rough grinding using a 1000-mesh silicon carbide grinding wheel at a speed of 3000 r / min and a feed rate of 8 μm. The wafer thickness is reduced to 150μm at a speed of 100mm / min. During the grinding process, cooling grinding fluid (deionized water + 0.5% grinding aid) is continuously sprayed to control the temperature of the grinding area to not exceed 80℃. In the second step of fine grinding, the 3000-grit diamond grinding wheel is replaced, the rotation speed is increased to 4500r / min, and the feed rate is 2μm / min to further thin the wafer to the target thickness of 100μm. After grinding, the grinding machine is turned off and the coolant is stopped. The wafer and tape are removed from the suction cup and placed in a 120℃ heating plate for 5 minutes. After the tape adhesive layer is heated and softened, the tape is peeled off smoothly in a 90° direction at a speed of 50mm / min using an automatic peeling agent.

[0048] Grinding test: After grinding, the TTV (total thickness change) of the wafer was measured, and the test results are recorded in Table 1.

[0049] Residual adhesive test: After peeling off the tape, observe whether there is any residual adhesive on the wafer. The test results are recorded in Table 1.

[0050] Warpage test: The warpage of the polished wafer was tested using a laser interferometer wafer warpage tester, and the test results are recorded in Table 1.

[0051] Table 1. Performance test data of the semiconductor wafer thinning tape in Examples 1-12 and Comparative Example 1.

[0052] Referring to Table 1, and in conjunction with Example 1 and Comparative Example 1, it can be seen that Comparative Example 1 uses a TPU substrate. Due to insufficient rigidity, the wafer softens at high temperature, resulting in uneven stress on the wafer. Consequently, the TTV of the polished wafer is significantly higher than that of the polished wafer in this application. Furthermore, the high-temperature bonding force between TPU and the adhesive layer decreases, resulting in obvious adhesive residue. Its warpage is also higher than that of the polished wafer in this application.

[0053] Referring to Table 1 and in conjunction with Examples 1 and 4, it can be seen that this application improves the surface tension of the film by performing plasma treatment on the substrate film, thereby reducing the TTV and warpage of the wafer after grinding.

[0054] Referring to Table 1 and in conjunction with Examples 4 and 5-7, it can be seen that by introducing metallocene polyethylene into the substrate layer preparation, this application further improves the rigidity and uniformity of the substrate layer, resulting in a reduction in the TTV and warpage of the wafer after grinding to varying degrees.

[0055] Referring to Table 1 and in conjunction with Examples 6 and 8-10, it can be seen that this application uses a combination of nano-silica, methacryloxyPOSS, and acrylate-terminated polydimethylsiloxane as modifiers. Compared with a single acrylate-terminated polydimethylsiloxane, the three work together to construct a composite structure of rigid skeleton-flexible connection-gap filling, which improves the wafer's fixation reliability and protection during the polishing process, and further reduces the TTV and warpage of the wafer after polishing.

[0056] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A tape for thinning semiconductor wafers, characterized in that, It includes a substrate layer and an adhesive layer disposed on the surface of the substrate layer, wherein the substrate layer is made of polyolefin and the adhesive layer is a modified acrylic adhesive layer; The modified acrylic adhesive layer comprises the following raw materials in parts by weight: 60-70 parts of isooctyl acrylate, 15-25 parts of butyl acrylate, 5-10 parts of methyl methacrylate, 2-5 parts of hydroxyethyl acrylate, 0.5-2 parts of glycidyl methacrylate, 1-3 parts of modifier, 0.8-1.2 parts of isocyanate crosslinking agent, 0.3-0.8 parts of epoxy crosslinking agent, and 0.3-0.8 parts of azobisisobutyronitrile.

2. The semiconductor wafer thinning tape according to claim 1, characterized in that, The polyolefin is one of polyethylene and polypropylene.

3. The semiconductor wafer thinning tape according to claim 2, characterized in that, The substrate layer is prepared by: extruding and casting linear low-density polyethylene to obtain a film, and then subjecting the film to plasma treatment under conditions of vacuum of 20-30 Pa, oxygen flow of 15-20 sccm, and radio frequency power of 100-120 W to obtain the substrate layer.

4. The semiconductor wafer thinning tape according to claim 2, characterized in that, The substrate layer is prepared by mixing linear low-density polyethylene, metallocene polyethylene and hindered phenolic antioxidant in a mass ratio of (88-90):(10-12):(0.03-0.05) and extruding and casting to obtain a film. The film is then subjected to plasma treatment under vacuum conditions of 20-30 Pa, oxygen flow rate of 15-20 sccm and radio frequency power of 100-120 W to obtain the substrate layer.

5. The semiconductor wafer thinning tape according to claim 1, characterized in that, The modifier comprises the following raw materials in parts by weight: 0.5-1.5 parts acrylate-terminated polydimethylsiloxane, 0.3-0.8 parts methacryloxyPOSS and 0.3-1.0 parts hydroxylated nanofiller.

6. The semiconductor wafer thinning tape according to claim 5, characterized in that, The modifier is prepared by adding hydroxylated nanofiller into a solvent and dispersing it ultrasonically, then adding methacryloyloxy POSS and stirring and dispersing it ultrasonically, and finally adding acrylate-terminated polydimethylsiloxane and dispersing it ultrasonically to obtain the modifier.

7. The semiconductor wafer thinning tape according to claim 6, characterized in that, The preparation method of the hydroxylated nanofiller is as follows: nano-silica is prepared by sol-gel method, and then surface modification is performed using silane coupling agent.

8. The semiconductor wafer thinning tape according to claim 6, characterized in that, The preparation method of the hydroxylated nanofiller is as follows: nano-silica and nano-alumina are prepared by sol-gel method, and then the nano-silica and nano-alumina are mixed and surface modified by silane coupling agent.

9. A process for preparing a semiconductor wafer thinning tape as described in any one of claims 1-8, characterized in that, Includes the following steps: Mix the monomer, solvent, and initiator according to the formula, react at 60-70℃ for 4-6 hours under nitrogen protection, raise the temperature to 75℃ and keep it at that temperature for 1 hour; cool down to below 40℃, add the modifier and crosslinking agent and stir evenly to obtain the adhesive. The adhesive is applied as a base coat to the substrate layer using a microgravure coating method, and then as a top coat using a transfer coating method to obtain a tape for thinning semiconductor wafers.

10. The manufacturing process of the semiconductor wafer thinning tape according to claim 9, characterized in that, Before coating, the substrate layer is subjected to corona treatment at a power of 300-350W and a speed of 10-15m / min.

Citation Information

Patent Citations

  • Photocuring wafer grinding protective adhesive tape, preparation method thereof and wafer thinning method

    CN119019947A

  • Adhesive, wafer cutting protective film and preparation method and application of wafer cutting protective film

    CN112724888A

  • Cutting adhesive tape for wafer as well as preparation method and application of cutting adhesive tape

    CN115181510A

  • POSS (Polyhedral Oligomeric Silsesquioxane)-based acryloyloxy hyperbranched polyethylene and application of POSS-based acryloyloxy hyperbranched polyethylene in graphene / carbon nanotube hybrid electric heating coating

    CN115850608A

  • POSS (Polyhedral Oligomeric Silsesquioxane) modified acrylic acid adhesive, preparation method thereof and application of POSS modified acrylic acid adhesive to battery cell blue film

    CN116179124A

Cited By

  • Non-UV wafer BG thinning adhesive tape and preparation method thereof

    CN122146179A

  • Non-uv wafer bg thinning adhesive tape and preparation method thereof

    CN122146179B